Oxidative stress-related biomarkers in multiple sclerosis: a review. (August 2016) - Ibitoye, Richard; Kemp, Kevin; Rice, Claire; Hares, Kelly; Scolding, Neil; Wilkins, Alastair
Aim: To provide an up-to-date review of oxidative stress biomarkers in multiple sclerosis and thus identify candidate molecules with greatest promise as biomarkers of diagnosis, disease activity or prognosis.Method: A semi-systematic literature search using PubMed and other databases.Results: Nitric oxide metabolites, superoxide dismutase, catalase, glutathione reductase, inducible nitric oxide synthase, protein carbonyl, 3-nitrotyrosine, isoprostanes, malondialdehyde and products of DNA oxidation have been identified across multiple studies as having promise as diagnostic, therapeutic or prognostic markers in MS.Conclusion: Heterogeneity of study design, particularly patient selection, limits comparability across studies. Further cohort studies are needed, and we would recommend promising markers be incorporated into future clinical trials to prospectively validate their potential.